1974
DOI: 10.1007/bf00388620
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite and tissue sterilization

Abstract: Trace amounts of sodium hypochlorite that remain on the surface of seeds (Lycopersicon esculentum Mill.) after sterilization interfere with subsequent uptake and incorporation of leucine into protein when the seeds are used in metabolic studies. The hypochlorite can be washed away with 0.01 N HCl but not by washing several times with water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Seeds of lettuce (Lactuca sativa, var. Reine de Mai, pleine terre) were stirred for 30min in commercial sodium hypochlorite (1SOg of Cl/litre), rinsed for 10min in a Biichner funnel with 41itres of sterile water, stirred for 5min in 0.01 M-HC (Abdul-Baki, 1974) and rinsed again for 15min with 6litres of sterile water. After this treatment, there was no bacterial or fungal contamination as checked by plating-out ground seeds on a medium containing (in 1 litre) Bacto yeast extract, 3 g; bactopeptone, 5g; agar, 15g; glucose, lOg; final pH, 7.3.…”
Section: Materials and Methods Lettuce Seedsmentioning
confidence: 99%
“…Seeds of lettuce (Lactuca sativa, var. Reine de Mai, pleine terre) were stirred for 30min in commercial sodium hypochlorite (1SOg of Cl/litre), rinsed for 10min in a Biichner funnel with 41itres of sterile water, stirred for 5min in 0.01 M-HC (Abdul-Baki, 1974) and rinsed again for 15min with 6litres of sterile water. After this treatment, there was no bacterial or fungal contamination as checked by plating-out ground seeds on a medium containing (in 1 litre) Bacto yeast extract, 3 g; bactopeptone, 5g; agar, 15g; glucose, lOg; final pH, 7.3.…”
Section: Materials and Methods Lettuce Seedsmentioning
confidence: 99%
“…Atlas 57 were obtained from R. Henke, Department of Botany, University of Tennessee. The seeds were dehusked with 50% H2 SO4 for 30 rain, rinsed with H2 O, placed in an agitated aqueous 1% CaCO3 mixture for 30 minutes, sterilized with 1.05% NaOC1 for 10rain, rinsed with sterile H20, placed in a flask which contained sterile 0.1 N HC1 for 10rain [1] and then rinsed three more times with sterile H20. The sterilized seeds were transferred to 25 x 150mm culture tubes containing 25mls of BM-1.…”
Section: Seed Sterilization and Growth Of The Explant Sourcementioning
confidence: 99%
“…In the propagation of the species listed in Table 1, the most commonly used agent was NaOCl which has an oxidative effect, and can break seed dormancy by partial degradation of the seed coat (Lee et al, 2007) and the oxidation of inhibitors of seed germination (Frank, Larson, 1970, Miyoshi, Mii, 1995. However, NaOCl can be toxic to plant tissue if it remains on the seed surface after rinsing, influencing the incorporation of amino acids into proteins (Abdul-Baki, 1974). Investigations of the influence of NaOCl on seed germination showed that results can be different depending on the species, solution concentration and duration of the treatment (Khah i Passam, 1992, Watkinson, Pill, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…У већини анализираних протокола (табела 1) коришћен је NaOCl који је оксидативно средство, и његов позитиван ефекат се огледа у прекидању дормантности семена растварањем и оксидацијом инхибитора клијања (Frank, Larson, 1970, Miyoshi, Mii, 1995, али и у делимичној деградацији семењаче (Lee et al, 2007). Међутим, не треба заборавити да NaOCl може имати и токсично дејство на биљно ткиво, јер уколико је заостао на површини семена након испирања, може да утиче на уграђивање аминокиселина у протеине (Abdul-Baki, 1974). Конкретан утицај NaOCl на клијање семена је истраживан, а добијени резултати се разликују пре свега зависно од испитиване врсте, затим од концентрације раствора, као и од дужине третирања семена (Khah i Passam, 1992, Watkinson, Pill, 1998.…”
Section: размножавање угрожених врста каранфилаunclassified